A portable smartphone-assisted ratiometric fluorescence sensor for intelligent and visual detection of malachite green. (1st March 2022) - Yue, Xiaoyue; Li, Yan; Xu, Sheng; Li, Junguang; Li, Min; Jiang, Liying; Jie, Mingsha; Bai, Yanhong
Graphical abstract: Highlights: A portable smartphone-assisted fluorescence sensor was developed for MG detection. Al-MOF and Rhodamine B were used to fabricate a ratiometric fluorescent sensor. A paper-based analytical device was integrated with the smartphone. The intelligent and visual analytical method showed satisfactory detection results. Abstract: Developing intelligent, sensitive, and visual methods for rapidly detecting veterinary drug residues is essential for ensuring food quality and safety. A portable smartphone-assisted ratiometric fluorescent sensor was successfully designed using fluorescent Al-MOF nanosheet and rhodamine B (RhB) as fluorescent probes to adjust to the requirement of malachite green (MG) detection. The developed ratiometric fluorescent sensor allowed sensitive and selective detection of MG with good linear relationships in a wide range of 0.5–200 μg/mL. The Quantitative linear range is 5.3 μg/mL to 200 μg/mL. The limit of detection (LOD) and limit of quantification (LOQ) were calculated to be 1.6 μg/mL and 5.3 μg/mL respectively. The practicability of the proposed method was verified using high performance liquid chromatography (HPLC) in spiked fish tissues with satisfying recoveries and RSD. Moreover, portable smartphone-assisted fluorescent test papers were fabricated for the intelligent detection of MG. This integration of smartphones and fluorescent test papers was economical and saved time, providing an alternative strategy for the qualitative discernment and semi-quantitative analysis of MG on-site.